Efficient synthesis of fused 1,2,3-triazolo-delta-lactams using huisgen [3+2] dipolar cycloaddition ``click-chemistry'' in water - Kumar, Indresh; Rode, Chandrashekhar V. (Chemistry Letters, 2007)
A general approach for the quick synthesis of various 1,2,3-triazolo-delta-lactams has been described, which involves the Huisgen [3 + 2] dipolar cycloaddition of azides derived from different amino acids with dimethyl acetylenedicarboxylate in water followed by cyclization.

Facile and highly selective deprotection of tert-butyldimethyl silyl ethers using sulfated SnO2 as a solid catalyst - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Rode, Chandrashekhar V. (Synthetic Communications, 2008)
Highly selective deprotection of tert-butyldimethylsilyl ethers at room temperature has been described using sulfated SnO2 as an efficient solid catalyst.
Keywords: deprotection; sulfated SnO2; TBDMS ethers

Functionalization of single-walled carbon nanotubes with azides derived from amino acids using click chemistry - Kumar, Indresh; Rana, Sravendra; Rode, Chandrashakher V.; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2008)
Single-walled carbon nanotubes (SWCNTs) were chemically functionalized with amino acid-based moieties. The covalent functionalization of alkyne-derived SWCNTs with well defined azides derived from amino acids was accomplished through Cu(I)-catalyzed Huisgen [3+2] dipolar cycloaddition click chemistry. Transmission electron microscopy, Raman spectroscopy, and infrared spectroscopic measurements confirmed the functionalization of SWCNTs by organic molecules derived from amino acids, and the resulting material showed some good solubility in the organic solvents such as tetrahydrofuran, CH2Cl2, and CHCl3.
Keywords: Amino acids; Carbon nanotubes; Click chemistry; Functionalization

Phosphotungstic acid on silica with modified acid sites as a solid catalyst for selective cleavage of tert-butyldimethylsilyl ethers - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Catalysis Communications, 2008)
The strength and nature of acid sites of bulk phosphotungstic acid could be modified after dispersing it on silica support which was characterized by XRD, ammonia TPD and (31)P MAS NMR techniques. This solid acid catalyst was found to be highly selective for the cleavage of tert-butyldimethylsilyl ethers at room temperature. The catalyst was easily recovered by filtration and could be reused for several times without loss of any activity giving a TON of 9.5 x 10(5). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Catalytic cleavage; reaction pathway; solid acid; tert-butyldimethylsilyl ethers; XRD

Assembly of gold nanoparticles on single-walled carbon nanotubes by using click chemistry - Rana, Sravendra; Kumar, Indresh; Yoo, Hye Jin; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2009)
Azide moiety-functionalized gold nanoparticles were conjugated with acetylene functionalized single-walled carbon nanotubes by employing copper-catalyzed Huisgen's [3+2] dipolar cycloaddition `click chemistry' reaction. Evidences of conjunction were observed by TEM, EDX and Raman images.
Keywords: Carbon nanotubes; Click chemistry; Functionalization; Nanoparticles

Photodegradation of EPDM/MWCNT nanocomposites: effect of singlet oxygen - Kumar, Bijandra; Kumar, Indresh; Singh, R. P. (Polymer Composites, 2009)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/multiwall carbon nanotubes (MWCNT) nanocomposites has been studied under accelerated UV-irradiation (lambda >= 290 nm) in the presence of singlet oxygen. The rate of photodegradation of EPDM/MWCNT is found to be higher when compared to the pristine polymer in presence of singlet oxygen. The enhancement of the rate of degradation of composite has been described through [2 + 2] photocycloaddition reaction between singlet oxygen and double bonds on composite which is followed by cleavage. The rate of degradation and the formation of new functional groups on the composite has been monitored by FTIR spectroscopy and found to be increased with irradiation time. The changes in surface morphology have been studied by scanning electron microscope. Differential scanning calorimetry measurements revealed an increase in the glass transition temperature of photodegraded EPDM and EPDM/MWCNT nanocomposites. POLYM. COMPOS., 30:855-860, 2009. (C) 2008 Society of Plastics Engineers

Proline catalyzed direct diastereoselective 6-enolexo aldolization: toward the synthesis of the imino sugar DNJ - Kumar, Indresh; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
A L-proline catalyzed direct diastereoselective 6-enolexo aldolization reaction of differentiating dialdehydes derived from tartaric acid is presented This organocatalytic approach provides high levels of synselectivity (dr > 10 1) with the stereocontrolled C-C bond formation between C4 and C5 intramolecularly which can serve to synthesize Imino-sugar skeleton quickly (C) 2010 Elsevier Ltd All rights reserved

Synthesis and characterization of polyurethane-grafted single-walled carbon nanotubes via click chemistry - Rana, Sravendra; Cho, Jae Whan; Kumar, Indresh (Journal of Nanoscience and Nanotechnology, 2010)
Polyurethane (PU)-grafted carbon nanotubes were synthesized by the coupling of alkyne moiety decorated single walled carbon nanotube (SWCNT) with azide moiety containing PU using Cu(I) catalyzed Huisgen [3 + 2] cycloaddition click chemistry. The azide moiety containing poly(E-caprolactone)diol was synthesized by ring-opening polymerization and further used for PU synthesis. Alkyne-functionalizion of SWCNT was completed by the reaction of p-aminophenyl propargyl ether with SWCNT using a solvent free diazotization procedure. Nuclear magnetic resonance, Fourier transform infrared, and Raman spectroscopic measurements confirmed the functionalization of SWCNT. Scanning electron microscopy and transmission electron microscopy images showed an excellent dispersion of SWCNTs, and specially debundling of SWCNTs could be observed due to polymer assisted dispersion. A quantitative grafting was successfully achieved even at high content of functional groups.
Keywords: Carbon nanotubes; Click chemistry; dispersion; polyurethane

Synthesis of hybrid 1,2,3-triazolo-delta-lactams/lactones using Huisgen [3+2] cycloaddition `click-chemistry' in water - Kumar, Indresh; Rana, Sravendra; Cho, Jae Whan; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
The synthesis of a new class of hybrid 1,2,3-triazozlo-delta-lactams/lactones has been achieved using the Huisgen [3+2] dipolar cycloaddition `click-chemistry' reaction of various organic azides with an activated alkyne in water, followed by cyclization. (C) 2010 Elsevier Ltd. All rights reserved.